Aplicação de nanotecnologia na remediação ambiental: Uso de nanopartículas de ferro zero valente (NZVI) em materiais contaminados - Fonseca, Rita (2019)
We performed a laboratorial test with the aim of evaluating the effect of the application of nanotechnology in the decontamination of soils and alluvium with high levels of metals (Zn, Cu, Cr, Co, Cd, Pb, Ni ) and As. An injection of a suspension of nanoparticles of zero-valent iron (nZVI) with 3 different concentrations (1 g/L, 3g/L and 7g/L), was used. For most of the elements the retention by nZVI was proportional to the concentration of the injected suspensions and the evolution was similar.The metals were immobilized by adsorption on the surface layer of iron oxides covering the nZVI and/or by mechanisms of complexation (co)-precipitation and chemical reduction. After 60 days of injection, the nZVIs lost their reactivity, and the retained species were desorbed and passed back to the soluble phase, a situation which was observed after 120 days. The evaluation of the effectiveness of the nanoparticles in these contaminated materials was positive, although the lost of reactivity 60 days after the injection. The low permeability of most materials makes difficult the injection and diffusion of nZVI, so a more efficient technique will be the use of macroparticles of zero-valent iron, more stable and as filling of reactive barriers.